Behavioural and social drivers of human papillomavirus vaccination in eThekwini District of KwaZulu-Natal Province, South Africa. - P Bhengu; D Ndwandwe; S Cooper; P D M C Katoto; C S Wiysonge; M Shey (PLoS ONE)
Background Cervical cancer is the second most common cancer in women in South Africa. Infection with high-risk types of human papillomavirus (HPV) is the cause of cervical cancer, which can be prevented by HPV vaccination. However, there is wide variation in HPV vaccination coverage among the urban districts of South Africa; with the lowest coverage being 40% in eThekwini, KwaZulu-Natal. There could be many factors which affect HPV vaccine uptake in eThekwini District. Thus, this research aims to investigate the behaviourial and social drivers of HPV vaccination in this district. Methods The study will consist of two phases. We will apply a convergent parallel mixed methods approach, including a quantitative survey (phase 1) and in-depth interviews (phase 2) among caregivers and frontline healthcare workers to determine the drivers of HPV vaccination uptake. Discussion The study will provide knowledge on the main barriers facing HPV vaccination and provide contextually-tailored solutions for how these barriers might be addressed. A policy brief will be formulated from this study aimed at government policymakers and other stakeholders who formulate or influence policy, respectively. In addition, we will disseminate the findings through peer-reviewed publications in scientific journals.